Ski world cup in safety in the context of coronavirus disease 2019 (COVID-19) pandemic - Villa, A.; Boccardi, M.; Fiocchi, M.; Szarpak, L.; Ilesanmi, O. (Journal of Health and Social Sciences, 2021)
Introduction: In the current pandemic scenario, it is necessary to ensure the health and safety of athletes, teams, and participants of competitive skiing events. This paper aimed to report a health and safety protocol for the Ski World Cup races experimented in Italy during the second wave of the COVID-19 pandemic. Methods: A protocol was developed for the prevention of COVID-19 infection among participants at skiing competitive races conducted at Santa Caterina and Bormio cities, Lombardy region, Italy in December 2020. The protocol was based on the recommended preventive measures issued from the public health community and indications reported by the Italian Sports Medical Federation (FMSI) protocol. A self-reported questionnaire was administered to participants. Antigenic swab tests were carried out `on-site`. Medical examinations were performed, when required. Descriptive analyses were carried out. Results: One thousand three hundred and ninety (91.6%) out of 1,518 participants were accredited. Only one of the 694 swab tests performed on-site for accreditation turned positive in an asymptomatic subject and was confirmed by molecular swab test. During the events no suspected case of COVID-19 was reported to the LOC. At the end of the two sporting events, antigen swabs were performed on 50 participants, and these yielded negative results. No COVID-19 positive case was reported in the next 14 days after the end of the games. Discussion and Conclusion: In Italy, the application of a protocol based on a self-administered questionnaire with a combination of antigen tests was effective for the reopening of elite skiing activity in Santa Caterina and Bormio during the second wave of the COVID-19 pandemic in Italy.